Design of a new concept of recycle trash bin - Mohd Fakhri Azizi, Jusoh (2008)
Recycling can be defined as the “act of processing used or abandoned materials for use in creating new products”. A recycling bin is a container which used to keep garbage or disposed item before being act by the respective authority to bring it the recycling centre. Recycling bins can be found in various forms and sizes. Nowadays, there are a lot of models of recycle trash bin which do not have the correct specification and yet have the disadvantage. The trash was not compacted, so it will requires a lot of space at the landfill. As a result, some of the landfill cannot afford to take all the trash. Part of the objective of this project is to overcome the problems occur nowadays by fabricating and designing the new concept of the recycle trash bin. The main scopes of this research are for two type of trasher, which are the 325ml cans and 600ml bottles. The design of the new concept of recycle trash bin for this project is basically from the research of existing models found in the current market. It comes with the lots of advantages from two major models, which are “separated trash model” and “un separated trash model”. The main materials that being use to fabricate the recycle trash bin is metal. The cover of recycle trash bin is made from acrylic. In creating and fabricate the recycle trash bin it will use a lot of machines. After the fabrication process, this recycle trash bin will be able to compact the trash successfully. Compare to the other model that exists in today’s market, this new recycle trash bin in more suitable for the use of the household. It is because the size of this recycle trash bin is smaller and the specialty is that in one recycle trash bin, consumer will found two different containers. So it will able to reduce the space used. The shaft will connect to the compactor and the handle shaft of the recycle trash bin can support the load when being use to compress the trash. There are no failures found during compacting the trash. As the conclusion from this project, this new design of recycle trash bin will be able to help and overcome the problems occurs nowadays and give advantages to users.